Bilinear forms, Schur multipliers, complete boundedness and duality - Christensen, Erik (MATHEMATICA SCANDINAVICA, 2023)
Grothendieck's inequalities for operators and bilinear forms imply some factorization results for complex $m × n$ matrices. Based on the theory of operator spaces and completely bounded maps we present norm optimal versions of these results and two norm optimal factorization results related to the Schur product. We show that the spaces of bilinear forms and of Schur multipliers are conjugate duals to each other with respect to their completely bounded norms.